PERSEPSI DAN PARTISIPASI PEMERINTAH DESA DALAM PERENCANAAN PENGEMBANGAN BUMDES DI KECAMATAN KENDAWANGAN - Asti Asti; Irfan Cholid (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
Village government participation is influenced by the mindset and views on BUMDes. The aims of the research is to find out the perception and participation of the village government in the development of BUMDes in Kendawangan District. The samples were taken by purposive sampling, with a total sample of 50 respondents Method of data analysis in this research by using scale interval of class. The results showed that the perception of Village Government to BUMDes development has been good, which shows village government agree that BUMDes as efforts acceleration of rural economic. The participation level of village government to BUMDes development was high, based on the formulation of BUMDes development which have been conducted by each village. The village government also have been allocated budget of BUMDes in ADD.